LEGAL STANDING OF LAND OWNERSHIP FOR MIXED-MARRIAGES BETWEEN BALINESE WIVES AND FOREIGN HUSBANDS IN BALI - Mirabel, Aurellia Valeda (Lex Prospicit, 2024)
The influx of foreign visitors to Bali has naturally led to increased interaction between foreign nationals and the local Balinese population. With mixed-marriages, there are special provisions for the nationality of the spouse, the nationality of the spouse, the nationality of the children, and property in the marriage.  Therefore, awareness is needed, especially for people of mixed-marriages to understand the provisions that apply to mixed-marriage spouses. This study uses normative juridical law which is a normative legal approach. The research emphasises the need for foreign nationals to understand the special provisions and restrictions for land ownership compared to Indonesian citizens. The Basic Agrarian Law of Indonesia (UUPA) governs land ownership regulations for mixed-marriages in Bali. Foreigners in Bali can acquire the right to use land through a Right to Use (Hak Pakai) or enter into leasehold agreements with Indonesian citizens or legal entities following to asas nasionalitas. However, land ownership rights are reserved exclusively for Indonesian citizens involved in mixed-marriages. The research highlights the influence of Hukum Adat, Balinese customary law, on land ownership in Bali. Mixed-marriage spouses should be aware of the regulatory disparities that arise after marriage and necessitate the arrangement of asset division. The customary law in Bali is in line with the existing statutory law in Indonesia.